Study of Planktonic Foraminferal biostratigraphy and depositional environment of Khasib, Tanuma and Saadi Formations in well Agel -12- Northeastern Tikrite - Al-Juboury, Faris; Al-Tharb, Muthana (Iraqi Journal of Science, 2023)
The present study deals with the biostratigraphy and depositional environment of(Late Turonian – Early Campanian) represent dy Khasib, Tanuma and SaadiFormations in well Agel -12- Northeastern Tikrite. Determination of threemicrofacies in Khasib, one microfacies in Tanuma and three microfacies in SaadiFormations. Depending on microfacies the paleoecologe of Khasib Middle shelf –Upper Bathyal environment, Tanuma Shelf Margin environment and SaadiFormations sediment in Middle shelf – Upper Bathyal. Twenty planktic foraminiferal species belonging to eight genera have been identified within thestudied well.Depending on the stratigraphic distribution of planktic foraminiferal species, thesuccession was divided into five biozones. These zones are correlated (locally andregional) with similar planktic foraminiferal1- Marginotruncana sigali interval Zone.2- Dicarinella primitive interval Zone.3- Dicarinella concavata interval Zone.h4- Dicarinella asymetrica Total Range Zone.5- Globotruncanita elevata Partial Range Zone.Age of Khasib Late Turonian, Tanuma Coniacian and Saadi Santonian - EarlyCampanian.